Pengembangan Desa Wisata Tapian Halaman Kampung sebagai Upaya Meningkatkan Ekonomi Masyarakat Lokal - Gustimal Witri; Tabliqh Deo Faturrahman; Ridho Sipangkar; Nyimas Dwi Fania Riskiana; Nada Naffisa Amalia; Novi Eka Rahayu; Yohana Dwi Nita; Rahmat Zega; Yunita Magdalena Silalahi; Usep Sofyan; Melda Lestari (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2023)
Sungai Petai village has a tourism sector that has the potential to build the economy and community welfare. The Tapian hometown tourist area has been open since 2022. There is still much work to be done in this tourist area. Currently, the Tapian area of the hometown provides tourism with various facilities. Among them are facilities like gazebos, Street Food, and baths. Our goal in serving Sungai Petai Village, especially in the Tapian Halaman Kampung Tourism Area, is to develop existing tourism potential. To create a good area or tourist village, it is better to continue to carry out more intense development. This is intended to attract visitors who will come to the tourist area. Our service results in creating creative waste education boards and promotional videos for tourism. With this, it is hoped that it can help increase public awareness of cleanliness in villages and tourist attractions and improve the quality of tourist areas in the village so that it can open up many jobs in these places. Thus, the economy of local communities will experience an increase.